ANALISIS DATA HASIL BELAJAR PAI SEBELUM & SESUDAH MENERAPKAN MODEL PEMBELAJARAN PROBLEM-BASED LEARNING (PBL) DI KELAS V - B. Siti Mardliyah; Fenia Marliana; Yulida Fauziyah; Rahayu Kariadinata; Elis Ratna Wulan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This research is motivated by the challenges in Islamic Religious Education (PAI) learning which is often still conventional and teacher-centered, thus not optimizing active involvement and student learning outcomes, especially on zakat material. The focus of the problem in this study is to analyze the differences in learning outcomes of fifth-grade students at before and after the implementation of the Problem-Based Learning (PBL) model. The research method used is a quantitative approach with descriptive and inferential statistical analysis using paired two-sample tests. Important stages of the research include collecting pre-test and post-test data, normality tests, and hypothesis testing using the Wilcoxon Test because the data is not normally distributed. The results showed a significant increase in students' average scores from 67.60 to 79.77. Based on the Wilcoxon Test, a significance value of 0.000 was obtained, indicating a real difference in student understanding after the implementation of the PBL model. However, the N-Gain Score analysis showed an average score of 0.3837 which is included in the